2022
DOI: 10.3389/fneur.2022.913283
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Side Effects Following Vaccination Against COVID-19 Among Individuals With Multiple Sclerosis Treated With DMTs in Poland

Abstract: Background and ObjectivesSince vaccination against COVID-19 is available for over a year and the population of immunized individuals with autoimmune disorders is higher than several months before, an evaluation of safety and registered adverse events can be made. We conducted a large study of side effects following the COVID-19 vaccine among patients with multiple (MS) sclerosis treated with disease-modifying therapies (DMTs) and analyzed factors predisposing for particular adverse events.MethodsWe gathered da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…SARS-CoV-2 vaccines had side effects that could potentially increase disability in pwMS or trigger a relapse of the disease [ 25 27 ]; this is, however, a controversial topic [ 28 ]. For this reason, some patients have already rejected a fourth dose of vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 vaccines had side effects that could potentially increase disability in pwMS or trigger a relapse of the disease [ 25 27 ]; this is, however, a controversial topic [ 28 ]. For this reason, some patients have already rejected a fourth dose of vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current experiences have shown that broad immunization with currently available vaccines is safe and effective, reducing the risk of severe COVID-19, hospitalization, and death ( 19 ). Multiple studies have concluded that COVID-19 vaccines are safe for individuals with MS ( 20 22 ). Cases like the one we reported here are rare, and—based on current knowledge—the benefits of vaccination against SARS-CoV-2 far outweigh the potential risks.…”
Section: Discussionmentioning
confidence: 99%
“…One of the top worldwide hazards to public health has been highlighted as vaccine hesitancy, which has been a widespread issue in the civilized world for years. There is still hesitation to receive Covid-19 immunization despite the fact that the vaccine being available for more than a year ( 181 ). The establishment of faith in medical professionals and manufacturers of vaccines needs to be a priority.…”
Section: Vaccine Strategies Against Covid-19mentioning
confidence: 99%